EP 121. Motor sequence learning in patients with limb apraxia – The effects of long-term training. Issue 9 (September 2016) - Reitze, S.; Heisterüber, M.; Karni, A.; Gal, C.; Doyon, J.; King, B.R.; Classen, J.; Rumpf, J.- J.; Buccino, G.; Klann, J.; Binkofski, F.
Abstract : Background: Recent studies show that limb apraxia is often not recognized as a higher motor impairment in patients suffering from a stroke. Because it is adversely affecting every-day life and personal independence, a successful rehabilitation of apraxia is critical for personal well-being (Cappa et al., 2005; Dovern et al., 2012 ). Yet, evidence of an effective treatment approach with long-lasting effects and generalization to untrained actions is still missing (Binkofski and Klann, 2013; Dovern et al., 2011 ). One possible reason for the treatment-resistance of this neurological disorder may be a deficit in motor memory storage of (re-) learned motor acts. So far, however, such a hypothesis has not been tested. Objective: The present study aimed at assessing the ability of apractic stroke patients to acquire and retain a new motor sequence skill. Methods: Eleven stroke patients suffering from chronic upper limb apraxia participated in a four-weeks multiple session training program using a motor sequence learning paradigm. Patients were required to perform a standardized finger sequence movement task, which is a well-established paradigm to explore motor learning and procedural memory abilities (e.g.Doyon et al., 2009 ). Motor performance was recorded with a modified four-button PC gaming keypad (Belkin Razer Nostromo, Belkin, Playa Vista, USA) and analyzed using customized Matlab (MathWorks, Natick, USA) scripts. Motor sequence learning was measured in terms of speed and accuracy. According to the hypothesis of disturbed motor memory abilities, no training induced simultaneous improvement in both, speed and accuracy, was expected. Results: All patients improved in terms of speed in producing the learned finger sequence. While patients were slow at the beginning of the training program, nearly all ended up with performance within age related norms. In contrast, accuracy varied across sessions. The latter finding can be explained through the notion of stroke-specific capacity problems (improving one capacity at cost of another). Moreover and unexpectedly, most of patients showed clinical improvement of their apraxia symptoms. Conclusions: All of our patients with limb apraxia were able to improve the speed of producing novel motor sequences, while accuracy remained variable. Thus, the present findings did not unequivocally reveal that the ability to acquire a new motor skill was retained. Further studies must determine whether the unexpected improvement of apraxia in patients with stable deficits is causally and specifically related to motor sequence training.